Results of recording sonic waves by seismic stations in the territory of Karelia - Lebedev, A.A.; Sharov, N.V. (Geofizicheskiy Zhurnal, 2021)
In spite of a relatively low seismic activity level, the detailed study of Karelia is not only of theoretical, scientific interest, but is also of practical value which has increased markedly because there are big industrial complexes, gas pipelines and hydrotechnical facilities in the region. The results of recording sonic waves of various nature by stationary and mobile seismic stations are presented. For the observation period 2000—2020 an array of seismic data has been accumulated. In order to correctly understand the nature of the signals under consideration, it should be noted that North Karelia is known to belong to seismic regions, where 5-point earthquakes have taken place earlier. They were distinguished from earthquakes generated by frost cracking by both visual and instrumental data. They are known throughout Fennoscandia. This group comprises both tremors during frost cracking of the soil, primarily with a sharp change in temperature, and frost cracking of ice in inland water bodies. To decide on the nature of ground shaking, it is necessary to pay attention to such signs as the limited area of oscillations and the nature of the wave record. As a result of seismic monitoring of Karelia, the following frost quakes were also recorded: the passage of the bolidi, the take-off of an aircraft, blasting operations during the disposal of ammunition and mining in the immediate vicinity of residential areas and industrial facilities. A wide range of possible sources and examples of sound waveforms are shown. The data obtained indicate the possibility of some shocks with a force of up to 4ѕ5 points in the immediate vicinity of the place of registration, what should be considered in the routine processing of seismic events and seismic hazard assessment in the southeastern Fennoscandian Shield.